Reservation Policy of Government Issues in Manipur University - Devi, Leisangthem Binita (JOURNAL OF INDIAN EDUCATION, 2020)
The Reservation Policy in India is centered on the Constitutional Framework for reservation. The Constitution of India provides reservations in (political, educational and employment). Reservation is a form of affirmative action in which a percentage of seats are reserved in educational institutions, Government services and Political bodies of the State and Central. In this paper, policies of reservation of the Government of India (GoI) in higher education has been highlighted. In addition to that, the various policies related to reservation of seats and issues related to reservation in the Manipur University are also analysed and discussed. Further, the paper discusses the need to understand those issues and problems of reservation policies in higher education of Manipur University.